One last meal before hitting the road: a Spotted House Gecko, Gekko monarchus (Schlegel, 1836), as prey of a road-killed Paradise Flying Snake, Chrysopelea paradisi Boie, 1827, with a review of prey reported for the species. - Evan S.H. Quah; L. Lee Grismer (Department of Biology Victor Valley College, 2024)
Southeast Asia and Borneo, specifcally, are home to a rich diversity of snake species (Stuebing et al., 2014; Uetz et al., 2023). However, there is only limited knowledge on the natural history and behaviour of most species due to the rarity of certain species and limited basic ecological studies for others (Stuebing and Inger, 1999; Malkmus et al., 2002; Stuebing et al., 2014). A signifcant understanding of the natural history of snakes can be gleaned from their diet, which can inform us about their habitat preference, temporal activity patterns, and hunting behaviour. One way such data have been collected has been through the examination of road-killed specimens that contained prey items (Shine et al., 2007; Trembath and Fearn, 2008; Fearn and Trembath, 2009; Trembath et al., 2009; Mao et al., 2010; Parkin and Oliver, 2015; Carbajal-Márquez et al., 2019; Ortiz-Medina et al., 2022; Silva-Soares et al., 2022; Lalremsanga et al., 2023; Rödel et al., 2023).